Analisis Pengaruh Hard Skill, Soft Skill dan Spiritual Skill terhadap Produktifitas Kerja Dosen di Malang - Eni Farida; Rahayu Widayanti (STIE Malangkucecwara, 2014)
Lecturer personality aspect is important for the learning process, to establish the identity of the lecturer in the profession , as well as provide professional academic services to students. Quality service excellence is inseparable from the ability of hard skills, soft skills, and spiritual skills possessed by the lecturer. Quality service excellence is inseparable from the ability of hard skills, soft skills, and spiritual skills possessed by the lecturer. This increased capacity is crucial because the government has declared that education in Indonesia must be able to create an intelligent and competitive man who has high academic grades, a good attitude and be able to compete with human resources from abroad. The purpose of this study are: 1) Analyze simultan influence between hard skills, soft skills, and spiritual skills to work productivity lecturer, 2) Analyze the effect of partially between hard skills, soft skills, and spiritual skills to work productivity lecturer, and 3) Analyzing the dominant variable affecting productivity lecturer. This study uses the lecturer as respondents, primary data collection is done by distributing questionnaires to 86 lecturers at the 5 largest universities in the city of Malang. There are three independent variables were analyzed, namely: hard skills, soft skills, and spiritual skills, while the dependent variable is labor productivity lecturer. Data was analyzed using multiple linear regression analysis . The analysis showed there are significant either simultaneously or partially between hard skills , soft skills , and spiritual skills to work productivity lecturer . Spiritual skill variable has a dominant influence on the productivity of faculty work